THE EVOLUTION OF LEGISLATION WITHIN CROSS-BORDER COOPERATION IN EUROPE AND UKRAINE - Olena, Voloshchuk; Olha O., Barabash; Svitlana, Senyk; N., Skurativych Irina; M, Tsukan Oksana; Maksym M. Kolіsnyk (International Journal of Psychosocial Rehabilitation, 2020)
The article explores the impact of European legal acts on the evolution of Ukrainian legislation in the field of cross-border cooperation, as well as on the level of legislation and its implementation both in Europe and Ukraine. The paper applies methods of comparative and legal analysis to identify key factors of particular importance within the policy-making process in European trans-frontier cooperation. The peculiarity of such cooperation referes to actions of European Union as supranational entity that requires legal approximation at all levels (international, national and regional) in Europe. In Ukraine different actors provide institutional support to the implementation of the public regional policy at three basic levels - national, regional and local. Once can characterize each administrative level by the activities of actors within their own legal powers. The institutional development of cross-border cooperation bases on three pillars: first, the regulatory system, second, the regulation of mechanisms of interaction between authorities at different levels and third, the creation of a sufficient number in regard to effective institutions in order to promote cross-border cooperation and joint cross-border projects which involve enterprises, public organizations, non-state institutions, educational and science institutions, etc. The empirical analysis helped to improve the classification levels for implementation of cross-border cooperation in Europe and the legislation in Ukraine (1) acquis communautaire, 2) international legal agreement ratified by Ukraine, 3) intergovernmental agreements, 4) national legislation, 5) interregional agreements).